Use of the normalcy index for the assessment of abnormal gait in the anterior cruciate ligament deficiency combined with meniscus injury. Issue 14 (5th July 2020) - Liu, Xiaode; Huang, Hongshi; Ren, Shuang; Rong, Qiguo; Ao, Yingfang
Abstract: The normalcy index (NI) has been implemented by several studies as a simple index for quantitatively analyzing diffident gait abnormalities, such as children with cerebral palsy and idiopathic toe-walkers. However, whether the NI can be used in anterior cruciate ligament (ACL) deficiency with different types of meniscus injuries or not, has not been reported yet. In this study, 25 patients who combined different types of ACL and meniscus injuries were evaluated by the NI analysis. 12 healthy subjects were used to define the normal range of NI. The result showed that NI values of patients were significantly larger than the control group (P < 0.05). Meanwhile, the tendency of increasing NI values associated with increasing pathology were significant with only 5 subjects in the smallest group (Jonkheere-Terpsta test: P < 0.001). These results indicated that the NI was a concise yet effective tool to evaluate combined ACL and meniscus injury patients. Increasing severity degree of meniscus tears in ACL rupture patients is corresponded to increasing NI values. It also demonstrates that the proposed NI can be applied as a robustness factor to detect the discrepancy between healthy and patient subjects clinically, and has the potential in the quantitative evaluation of pre- or post-surgery and rehabilitation.